Efficacy of cilostazol in canine bradyarrhythmia - Ohmori, Takahiro; Matsumura, Yuri; Yoshimura, Aritada; Morita, Shohei; Hasegawa, Hiroshi; Hirao, Daiki; Fukushima, Ryuji (Frontiers in Veterinary Science, 2022)
Recently, cilostazol, a phosphodiesterase III inhibitor, has been described as alternative medical treatment for canine bradyarrhythmia in cases for which pacemaker implantation was not indicated or available. In this retrospective study, we investigated the use and efficacy of cilostazol in dogs with bradyarrhythmia in Japan. Dogs that had been brought to the Tokyo University of Agriculture and Technology Animal Medical Center and 23 veterinary hospitals in Japan and been treated with cilostazol initially as the only therapeutic strategy for bradyarrhythmia between January 2010 and August 2021 were included in this study. Survival analyses were performed using Cox proportional hazards analysis, the log-rank test, and the generalized Wilcoxon test to evaluate the efficacy of cilostazol. Fifty-nine privately owned dogs were included in this study. In the survival time analysis, the risk of death was significantly lower and the survival rate was higher in cases in which cilostazol was administered at 10 mg/kg or more per dose. A third-degree atrioventricular block also significantly increased the risk of death and was associated with a lower survival rate. However, in some patients with a third-degree atrioventricular block, there was an increase in the ventricular rate and improvement in clinical symptoms without disappearance or decrease of the atrioventricular block. This study had several important findings that have not previously been reported concerning the use of cilostazol for canine bradyarrhythmia, including the appropriate dose in a clinical setting and the efficacy and prognosis according to the type of bradyarrhythmia.